Trailer Cinema Africa 2024 (2024)
Please note: THIS TRAILER CONTAINS FLASHING LIGHTS THAT MAY AFFECT PHOTOSENSITIVE VIEWERS From January 21 to 24, 2024, the "Cinema Africa" film festival of the Cluster of Excellence "Africa Multiple" invites film and Africa aficionados alike to embark on a four-day trip through African narratives. The journey leads from south to north, from Tunisia to Lesotho, with stops in Burkina Faso, Nigeria and the Democratic Republic of Congo, and shows the broad spectrum of modern African cinema. All five films presented during the festival in Bayreuth impress with their unique cinematic aesthetics and extraordinary storytelling and have already attracted a lot of attention at international film festivals and received various awards. From Sunday, January 21 to Wednesday, January 24, 2024, the screenings will take place at Cineplex Bayreuth (always starting at 8 pm, on January 22 also at 6 pm). Each screening will be followed by an audience discussion.